Effect of Probiotic Supplementation on FSH, LH Levels and Folliculogenesis - Nur Rahman; Syarief Thaufik Hidayat; Besari Adi Pramono; Raden Soerjo Hadijono; Agoes Oerip Poerwoko; Arufiadi Anityo Mochtar (Journal of Biomedicine and Translational Research, 2023)
Background: Polycystic ovary syndrome (PCOS) is an endocrine disorder that often occurs in women of reproductive age. The main therapy currently used to treat PCOS patients is insulin sensitizer. In PCOS, there is an imbalance in the intestinal flora which causes activation of the immune system and an inflammatory response that leads to insulin resistance. The effect of probiotic supplementation on insulin resistance can have an impact on changes in reproductive hormone levels in PCOS women. Objective: Analyze the effect of probiotic supplementation on levels of FSH, LH, and folliculogenesis in a study of PCOS Wistar rats. Methods: Experimental research with a post-test only controlled group design. The research sample was 35 Wistar rats which were divided into 5 groups, (K-) were healthy rats, (K+) were PCOS rats without treatment, (P1) were PCOS rats received Metformin, (P2) were PCOS rats received Probiotics, and (P3) were PCOS rats that received Metformin + Probiotics. The intervention was carried out for 14 days. The dependent variables were levels of FSH, LH and folliculogenesis. Research data were analyzed using one-way ANOVA test, Fisher Exact test. Differences between groups and controls were tested with Dunnett's post hoc test. Significant p<0.05Results: Metformin + probiotic supplementation resulted in increased FSH levels, decreased LH levels and increased folliculogenesis when compared to the PCOS rats without treatment (K+).Conclusion: Metformin + probiotic supplementation causes levels of FSH, LH and folliculogenesis activity in PCOS rats to resemble healthy rats.